Friction stir welding of duplex and superduplex stainless steels and some aspects of microstructural characterization and mechanical performance (2016)
Friction stir welding was used to produce butt joints on 6 mm thick plates of UNS S32101 lean duplex stainless steel, S32205 duplex stainless steel, and S32750 and S32760 superduplex stainless steels. Fully consolidated joints were achieved, with full penetration, using heat input of 1.37-1.50 kJ/mm. Specimens submitted to tensile testing performed perpendicular to the welding direction showed failure on the base metal, reflecting better mechanical performance of the welded joints. Furthermore, tensile testing along the joints revealed higher yield and tensile strengths in all cases, as well as increased elongation. Microstructural evaluation showed that there was pronounced grain refinement in the welded joints of all the materials studied, achieving grain sizes as small as 1 µm. The differences in the ferrite and austenite grain sizes in the stir zone, such as the degree of grain refinement, could be explained by the combination of dynamic recrystallization of austenite during the welding process and the recrystallization and growth of the ferrite grains, promoted firstly by the severe deformation and secondly by the high temperature inherent to the FSW process. Superduplex stainless steel FSW joints were more able to maintain a balanced microstructure, compared to conventional and lean duplex stainless steels, due to greater homogeneity of recrystallization in the welded joint.